A Novel Soybean Dirigent Gene GmDIR22 Contributes to Promotion of Lignan Biosynthesis and Enhances Resistance to Phytophthora sojae - Li, Ninghui; Zhao, Ming; Liu, Tengfei; Dong, Lidong; Cheng, Qun; Wu, Junjiang; Wang, Le; Chen, Xi; Zhang, Chuanzhong; Lu, Wencheng; Xu, Pengfei; Zhang, Shuzhen (Frontiers in Plant Science, 2017)
Phytophthora root and stem rot caused by the oomycete pathogen Phytophthora sojae is a destructive disease of soybean worldwide. Plant dirigent proteins (DIR) are proposed to have roles in biosynthesis of either lignan or lignin-like molecules, and are important for defense responses, secondary metabolism, and pathogen resistance. In the present work, a novel DIR gene expressed sequence tag (EST) is identified as up-regulated in the highly resistant soybean cultivar ‘Suinong 10’ inoculated with P. sojae. The full length cDNA is isolated using rapid amplification of cDNA ends (RACE), and designated GmDIR22 (GenBank accession no. HQ_993047). The full length GmDIR22 is 789 bp and contains a 567 bp open reading frame encoding a polypeptide of 188 amino acids. The sequence analysis indicated that GmDIR22 contains a conserved dirigent domain at amino acid residues 43–187. The quantitative real-time reverse transcription PCR demonstrated that soybean GmDIR22 mRNA is expressed most highly in stems, followed by roots and leaves. The treatments with stresses demonstrated that GmDIR22 is significantly induced by P. sojae and gibberellic acid (GA3), and also responds to salicylic acid (SA), methyl jasmonic acid (MeJA), and abscisic acid (ABA). The GmDIR22 is targeted to the cytomembrane when transiently expressed in Arabidopsis protoplasts. Moreover, The GmDIR22 recombinant protein purified from Escherichia coli could effectively direct E-coniferyl alcohol coupling into lignan (+)-pinoresinol. Accordingly, the overexpression of GmDIR22 in transgenic soybean increased total lignan accumulation. Moreover, the lignan extracts from GmDIR22 transgenic plants effectively inhibits P. sojae hyphal growth. Furthermore, the transgenic overexpression of GmDIR22 in the susceptible soybean cultivar ‘Dongnong 50’ enhances its resistance to P. sojae. Collectively, these data suggested that the primary role of GmDIR22 is probably involved in the regulation of lignan biosynthesis, and which contributes to resistance to P. sojae.